(untitled) (Hekima Review, 2024)
Today, we face an unprecedented crisis of forced migration. Over 110 million persons have fled from their homes, almost 8 million in Sudan alone. In this essay, I will first briefly touch on the nature and scope of forced migration and then turn to the ethical questions posed by such displacement and the theological implications of “welcoming the stranger” in our midst. I will conclude by considering the place (rhetorical locus) of displacement in our Ignatian spirituality.